2018
DOI: 10.1007/s11596-018-1876-3
|View full text |Cite
|
Sign up to set email alerts
|

Drilling Combined with Adipose-derived Stem Cells and Bone Morphogenetic Protein-2 to Treat Femoral Head Epiphyseal Necrosis in Juvenile Rabbits

Abstract: This study was designed to evaluate the effects of drilling through the growth plate and using adipose-derived stem cells (ADSCs) and bone morphogenetic protein-2 (BMP-2) to treat femoral head epiphyseal ischemic necrosis, which can be done in juvenile rabbits. Passagefour bromodeoxyuridine (BrdU)-labeled ADSCs were cultured, assayed with MTT to determine their viability and stained with alizarin red dye to determine their osteogenic ability. Two-month-old, healthy male rabbits (1.2 to 1.4 kg, n=45) underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…It would be more appropriate to use human ADSCs from a clinical perspective. However, previous studies on ADSCs have demonstrated their effectiveness across several species [33][34][35] . Second, the severity of RA in our mouse model was evaluated on the basis of generalized clinical scoring.…”
Section: Discussionmentioning
confidence: 99%
“…It would be more appropriate to use human ADSCs from a clinical perspective. However, previous studies on ADSCs have demonstrated their effectiveness across several species [33][34][35] . Second, the severity of RA in our mouse model was evaluated on the basis of generalized clinical scoring.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in profound skin wounds, the remaining skin stem cells cannot experience normal differentiation capacity and complete the anatomical structure and functional skin repair according to the preprogrammed pathways. Therefore, the healing progression may be disrupted, ultimately developing scar tissue devoid of the hair follicle and sweat glands [ 4 ]. This indicates that the process of wound healing is associated with interaction among cells, complex regulation of the extracellular matrix, and various paracrine elements [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in profound skin wounds, the remaining skin stem cells cannot experience normal differentiation capacity and complete the anatomical structure and functional skin repair according to the preprogrammed pathways. Therefore, the healing progression may be disrupted, ultimately developing scar tissue devoid of hair follicle and sweat glands (4). This indicates that the process of wound healing is associated with interaction among cells, complex regulation of the extracellular matrix, and various paracrine elements (5).…”
Section: Introductionmentioning
confidence: 99%